La déesse Korè-Perséphone: mythe, culte et magie en Attique - Dimou, Alexandra (Brepols, 2016)
Duality of her nature is a salient trait of Greek goddess Kore-Persephone. It is reflected not only in her name but also in her fate. She moves perpetually between the Underworld and that of the Living, and between maidenhood and womanhood. This research focuses on the Kore-Persephone myth in Attica, how she was worshipped and how she was present even outside the civic religion. This work explores the myth of Kore, the etymology of her name according to ancient Greeks, how she was worshipped or celebrated in festivals in Attica, either alone or along with Demeter. Finally the author attempts to identify her role in magic, in the Dionysian or Orphic religious societies, and in Artemidorus’ oneirocritical treatise.